Summaries of plenary and selected symposia sessions at the XXIV World Congress of Psychiatric Genetics; Jerusalem, Israel; 30 October 2016–3 November 2016. (April 2017) - Ciobanu, Liliana G.; Ori, Anil P.S.; Pagliaroli, Luca; Polimanti, Renato; Spindola, Leticia M.; Vincent, John B.; Cormack, Freida K.
Abstract : The XXII World Congress of Psychiatric Genetics, sponsored by the International Society of Psychiatric Genetics, took place in Jerusalem, Israel, from 30 October 2016 to 3 November 2016. A total of 372 participants gathered to discuss the latest findings in the field. The following report was written by early career investigator travel awardees, and student and postdoctoral attendees. Each was assigned one or more sessions as a rapporteur. This manuscript represents topics covered in most, but not all of the presentations during the conference, and contains some of the major notable new findings reported.